Continuity and change in patriarchal cultural practices in Ihiala in the modern era - Esther Chiamaka Okezie (Humanities Horizon, 2026)
In most African cultures, patriarchal cultures have remained relevant over the years regardless of the growing global focus on gender equality, which has left people questioning their applicability and effects on women in the modern societies. This research paper will look at continuity and transformation of patriarchal cultural practices of Ihiala during the modern era on how the traditional norms have been maintained, altered or even dropped with regards to modernization. It examines widowhood ceremonies, disinheriting, favoring male offspring, bride price, female circumcision and puts them in their historical and socio-cultural perspective. The paper will take a qualitative and historical approach, and it will use both primary sources, such as oral interviews, as well as secondary academic resources to examine these dynamics. The results indicate that although some patriarchal behaviours still exist in altered forms, there have been great changes with the impact of the western education, Christianity, legal reforms, media activism and globalisation. Evil customs like the observation of widowhood ceremonies and cutting of female genitals have been either dropped or criminalized and women have increasingly been allowed to get education, inheritance and even participate in decision making. Nevertheless, some forms of discrimination are still perpetuated by other entrenched cultural beliefs, financial reliance, and poor enforcement of institutions. The research findings conclude that the patriarchal cultural practices in Ihiala do not remain the same but are currently being negotiable between the tradition and modernity. Gender equality must be achieved through long-term efforts which may combine cultural sensitivity, legal and social reforms.